A murine model of peanut-allergic asthma - Paolucci, Marta; Antz, Nathalie; Homère, Valentine; Kolm, Isabel; Kündig, Thomas M.; Johansen, Pål (Frontiers in Allergy, 2024)
Objectives Peanut allergy is an IgE-mediated food allergy that is associated with asthma in certain patients. With increasing prevalence, its great impact on the quality of life, and a lack of treatment options, the need for new therapy options is a given. Hence, models for research and development are required. This study aimed to establish a murine model of allergic airway inflammation induced by peanut allergens. Methods C3H mice were sensitised by intraperitoneal injections of peanut allergen extract and challenged by an intranasal application of the same extract. The assessment of airway inflammation involved the analysis of immune cells in the bronchoalveolar lavage fluid as measured by flow cytometry. Inflammatory reactions in the lung tissue were also studied by histology and quantitative PCR. Moreover, peanut-specific immune responses were studied after re-stimulation of spleen cells in vitro. Results Sensitisation led to allergen-specific IgE, IgA, and IgG1 seroconversion. Subsequent nasal exposure led to allergic airway inflammation as manifested by structural changes such as bronchial smooth muscle hypertrophy, mucus cell hyperplasia, infiltration of eosinophil cells and T cells, as well as an upregulation of genes expressing IL-4, IL-5, IL-13, and IFN-γ. Upon re-stimulation of splenocytes with peanut allergen, increased secretion of both T-helper type 2 (Th2) and Th1 cytokines was observed. Conclusion We successfully established a peanut-associated asthma model that exhibited many features characteristic of airway inflammation in human patients with allergic asthma. The model holds potential as a tool for investigating novel therapeutic approaches aimed at preventing the development of allergic asthma.